The Prevalence of HLA-B*57 Serotype Associated with Hypersensitivity Reactions in the Treatment of HIV İnfection in the Turkish Population - Kizmaz, Muhammed A.; Simsek, Abdurrahman; Aymak, Figen; Akalin, Emin Halis; Oral, Haluk Barbaros; Budak, Ferah (Current HIV Research, 2023)
Objectives: The aim of our study is to reveal the prevalence of HLA-B*57 in the Turkish population and to provide new perspectives to physicians starting abacavir therapy in HIV patients.Background: Abacavir, one of the drugs used to treat HIV infection, can cause hypersensitivity reactions in some patients. These hypersensitivity reactions have been shown to be associated with the HLA-B*57:01 allele. High-resolution HLA-B*57:01 scanning has a time and cost disadvantage compared with low-resolution HLA-B*57 scanning. Before starting abacavir treatment, we will discuss whether high-resolution scanning is more beneficial in individuals who are positive on HLAB* 57 screening. This is the study with the largest cohort to investigate the prevalence of HLA-B*57 in Turkey.Methods: The results of 25 thousand 318 people who applied to Bursa UludaĦ#159; University Faculty of Medicine, Department of Immunology for HLA-B* typing were scanned.Results: In our study, the HLA-B*57 serotype was detected in 827 (3.3%) individuals.Conclusion: Considering these results, it can be assumed that the prevalence of HLA-B*57:01 in Turkey is lower than 3.3%. Instead of a high-resolution HLA-B*57:01 scan in all patients starting abacavir therapy, a high-resolution HLA-B*57:01 scan might be of greater benefit in patients who are positive on a low-resolution HLA-B*57 scan.
Keywords: hypersensitivity